1984
DOI: 10.1039/f19848003275
|View full text |Cite
|
Sign up to set email alerts
|

Stability constants of complexes of monensin and lasalocid with alkali-metal and alkaline-earth-metal ions in protic and polar aprotic solvents

Abstract: Measurements have been made of the stability constants of complexes of the anionic ionophores monensin and lasalocid with alkali-metal cations, alkaline-earth-metal cations and Ag+ in several solvents, both protic and polar aprotic. The complexes of monensin are very stable and show a sharp stability maximum among the alkali-metal cations for the Na+ complex in all solvents. Compared with complexes of various neutral ionophores, the stability constants of monensin complexes are relatively much higher in aproti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 2 publications
2
15
0
Order By: Relevance
“…In addition, the polar functionality of these compounds can orient toward the cation with the outer solvent accessible portion of the molecule being largely hydrophobic [44][45][46][47], resulting in some degree of metal encapsulation [6,46,48]. Monensin has a higher affinity for Na ϩ , K ϩ , Ca 2ϩ , and Mg 2ϩ , with a strong preference for sodium, whereas lasalocid has less affinity for all four cations and a slight preference for Mg 2ϩ , K ϩ , and Ca 2ϩ [51]. Monensin has a higher affinity for Na ϩ , K ϩ , Ca 2ϩ , and Mg 2ϩ , with a strong preference for sodium, whereas lasalocid has less affinity for all four cations and a slight preference for Mg 2ϩ , K ϩ , and Ca 2ϩ [51].…”
Section: Sorption Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the polar functionality of these compounds can orient toward the cation with the outer solvent accessible portion of the molecule being largely hydrophobic [44][45][46][47], resulting in some degree of metal encapsulation [6,46,48]. Monensin has a higher affinity for Na ϩ , K ϩ , Ca 2ϩ , and Mg 2ϩ , with a strong preference for sodium, whereas lasalocid has less affinity for all four cations and a slight preference for Mg 2ϩ , K ϩ , and Ca 2ϩ [51]. Monensin has a higher affinity for Na ϩ , K ϩ , Ca 2ϩ , and Mg 2ϩ , with a strong preference for sodium, whereas lasalocid has less affinity for all four cations and a slight preference for Mg 2ϩ , K ϩ , and Ca 2ϩ [51].…”
Section: Sorption Experimentsmentioning
confidence: 99%
“…This coordination gives ionophores the unique ability to transport metal ions across cell membranes as either undissociated acids or neutral complexes and gives the molecule a largely hydrophobic exterior [12,46,[48][49][50]. Monensin has a higher affinity for Na ϩ , K ϩ , Ca 2ϩ , and Mg 2ϩ , with a strong preference for sodium, whereas lasalocid has less affinity for all four cations and a slight preference for Mg 2ϩ , K ϩ , and Ca 2ϩ [51]. The differences in the coordination preferences of monensin and lasalocid may be responsible for the difference in the pH-dependent sorption of the two ionophores as well as the reason why phosphate was needed to enhance lasalocid recovery, but not for monensin recovery, from soil A1A2.…”
Section: Sorption Experimentsmentioning
confidence: 99%
“…Commonly, the polyethers are referred to as ionophores because of their ability to bind metal ions forming electrically neutral complexes able to cross the cell membranes. Monensin is known as a monovalent polyether ionophore since it readily complexes alkali ions with an affinity increasing in the order Cs + < Li + < Rb + < K + < Na + [18][19][20]. The crystallographic studies on a series of Monensin metal complexes showed the formation of shell-like complexes in the solid state [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 98%
“…The spectroscopic and X‐ray studies of lasalocid demonstrated that its structure in solutions and in the solid state11–23 is very similar. The same methods were used to determine the structure of lasalocid complexes with monovalent and divalent cations,15, 24–29 as well as with several asymmetric amine salts30 and amine acid ester salts 31–34…”
Section: Introductionmentioning
confidence: 99%